2007
DOI: 10.1080/00071660601161412
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between breeder age, egg cholesterol content, blood cholesterol level and hatchability of broiler breeders

Abstract: 1. The research was carried out to investigate correlations between breeder age, egg cholesterol content, blood cholesterol level and hatchability of broiler breeders. 2. Egg cholesterol content increased with increased breeder age. The mean yolk cholesterol contents (mg per g yolk) were 10.47+/-0.28, 15.34+/-0.65 and 15.64+/-0.71 mg/g at 28, 45 and 65 weeks of age, respectively. 3. There were positive correlations between yolk weight and yolk cholesterol content (mg/g yolk) (r=01.941; P<0.01) and egg choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
12
1
1
Order By: Relevance
“…Assuming equal carotenoid intake among age classes, the first possibility can thus be discarded. In contrast, intestinal absorption efficiency and blood transport may be influenced by the absorption and circulation of lipids, particularly cholesterol (Surai 2002;McGraw and Parker 2006), and evidence from poultry indicates that cholesterol levels increase with age (Dikmen and Sahan 2007). Oxidative stress in blood could also reduce the availability of carotenoids for pigmentation .…”
Section: Differences Between Ages and Environmentsmentioning
confidence: 99%
“…Assuming equal carotenoid intake among age classes, the first possibility can thus be discarded. In contrast, intestinal absorption efficiency and blood transport may be influenced by the absorption and circulation of lipids, particularly cholesterol (Surai 2002;McGraw and Parker 2006), and evidence from poultry indicates that cholesterol levels increase with age (Dikmen and Sahan 2007). Oxidative stress in blood could also reduce the availability of carotenoids for pigmentation .…”
Section: Differences Between Ages and Environmentsmentioning
confidence: 99%
“…However, to reduce cholesterol contents is not easy without reducing egg production and weight. Dikman and Saham (2007). According to recommendation by Leeson and Summers (2005), the laying hens aged 18 -32 weeks old need 20 g crude protein/hen/day and 260 Kcal ME/hen/day.…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to the significant effect of both maternal and paternal components (parents) on fertility and early embryo survival. Literature showed that hatchability reduction of eggs from older broiler breeders is a result of many contributing factors, including larger egg size (Leeson & Summers 2000), increased early and late embryo mortality (Elibol & Braket 2003), poorer shell quality due to bigger surface area (Bennett 1992), albumen quality deterioration (Tona et al 2004) and increased the yolk cholesterol content (Dikmen & Sahan 2007). Ransin (2005) provided the fertility and hatchability goals at certain ages of breeder flock.…”
Section: Effect Of Broiler Breeder Age On Fertility and Hatchability mentioning
confidence: 99%